Pengaruh Konten Pemasaran & Live Shopee Terhadap Keputusan Pembelian Pelanggan - Nita Apriliani; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2025)
In the digital era, marketing strategies through e-commerce have rapidly evolved. Shopee, as one of the leading platforms, utilizes marketing content and live streaming features as efforts to attract customers. This study aims to analyze the influence of marketing content and Shopee live streaming on customer purchasing decisions. The research employs a descriptive quantitative approach using a questionnaire as the instrument. The expected results indicate that engaging marketing content and interactive live streaming have a positive impact on consumer interest and purchasing decisions. These findings are expected to serve as a reference for businesses in optimizing their digital marketing strategies.